OPTIMASI LABA PADA HASIL PRODUKSI TENUN IKAT DI DESA TERNATE, KABUPATEN ALOR MENGGUNAKAN METODE SIMPLEKS - Isdarmayanti; Lalang, Damaris; Ena, Maktisen (Amalgamasi: Journal of Mathematics and Applications, 2025)
This study aimed to optimize the profit of ikat weaving production in Ternate Village, Alor Regency using the simplex method. The research focused on four types of woven products produced by the Pantai Laut weaving group, namely ikat sarongs, ikat shawls, ikat blankets, and a combination of blankets and shawls. The problem of maximizing production profit was formulated using linear programming and solved with the simplex method, supported by QM for Windows software. Primary data were obtained through direct interviews and observations with weavers to identify product prices and material costs. The mathematical model included an objective function to maximize profit and constraints based on the availability of three types of threads: cotton, misrais, and machine thread. The results showed that by using the available resources—22 heads of cotton thread, 25 heads of misrais thread, and 15 heads of machine thread—the optimal combination of products could yield a profit of IDR 4,255,000, with a total potential sales value of IDR 4,970,000. This finding demonstrates that mathematical optimization methods like the simplex method are effective tools for small-scale industries to allocate limited resources efficiently and increase income